Classical Radio OK by FCC (Raton Range Raton, NM, 1993)
About the Federal Communications Commission giving the Raton Arts and Humanities Council approval to construct and operate a radio translator station serving Raton rebroadcasting KHFM, an Albuquerque classical music station.
Newspaper article
Master list item #: 26
File location is in the Raton file Cabinet
Keywords: Donati, Marilyn -- Arts and Humanities Council Director; Erwin, Jackie -- Former Arts and Humanities Council Director; Federal Communications Commission; KHFM Radio; Radio Stations; Music and Entertainment; Arts and Humanities Council